2018
DOI: 10.1007/s00264-018-3889-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy of screw implantation could decrease the incidence of post-operative hydrothorax? O-arm navigation vs. free-hand in thoracic spinal deformity correction surgery

Abstract: The volume of PE after correction surgery can be significantly decreased by application of O-arm navigation system as compared to conventional free-hand technique. We ascribed the improvement to the accuracy of screw implantation navigated by O-arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study shows that the O-arm navigation aid technology can effectively improve the accuracy of screw placement. [ 5 ] Given the rapid rehabilitation and minimally invasive surgery concepts, the Wiltse approach can not only reduce tissue damage, but also play a positive role in reducing blood loss and increasing quality of life. [ 14 , 15 ] Here, a retrospective case-control study of 32 patients with AS combined with thoraco-lumbar fracture showed that pedicle screw reduction with O-arm navigation assisted by the Wiltse approach could significantly shorten operation time, reduce the amount of intraoperative bleeding volume, and improve the accuracy of pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that the O-arm navigation aid technology can effectively improve the accuracy of screw placement. [ 5 ] Given the rapid rehabilitation and minimally invasive surgery concepts, the Wiltse approach can not only reduce tissue damage, but also play a positive role in reducing blood loss and increasing quality of life. [ 14 , 15 ] Here, a retrospective case-control study of 32 patients with AS combined with thoraco-lumbar fracture showed that pedicle screw reduction with O-arm navigation assisted by the Wiltse approach could significantly shorten operation time, reduce the amount of intraoperative bleeding volume, and improve the accuracy of pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern technology and the concept of minimally invasive surgery, the O-arm is used more and more often during orthopedic surgery, since it facilitates intraoperative three-dimensional CT imaging and intraoperative real-time navigation, both of which greatly improve the accuracy of the screwing procedure. [ 5 7 ] However, to date there are few reports on O-arm navigation-assisted pedicle screw placement for AS combined with thoracolumbar vertebral fractures. The purpose of this study was therefore to examine the efficacy of an O-arm navigation-assisted Wiltse approach relative to a freehand posterior pedicle screw combined osteotomy in cases of AS combined with thoracolumbar fracture.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in a previous study, the nerve injury risk and clinical complications could be decreased through this technique [ 24 ]. Zhao et al [ 25 ] compared the occurrence of postoperative hydrothorax between O-arm navigation and free-hand in spinal deformity surgery. They found that the volume of postoperative hydrothorax could be significantly reduced using the O-arm navigation, and this was ascribed to the improvement in screw implantation accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There was a trend towards shorter length of hospital stay and lower blood loss in the navigation group in this study; although not statistically significant. Studies which have compared length of hospital stay and blood loss have shown as well non-significant trends towards a decrease compared to free-hand [28][29][30] . Our sample size is too small to detect any such differences in these secondary endpoints.…”
Section: Figurementioning
confidence: 99%